Związek wolnego rynku z dyktaturą polityczną: przejściowy czy trwały? Przykład Chin - Dylus, Aniela (Człowiek i Społeczeństwo, 2018)
Aniela Dylus, Związek wolnego rynku z dyktaturą polityczną: przejściowy czy trwały? Przykład Chin [The relation between free market economy and political dictatorship – is it of temporary or permanent nature? The example of China] edited by W. Banach, M.A. Michalski, J. Sójka, „Człowiek i Społeczeństwo” vol. XLVI: Między Chinami a Zachodem. Pytanie o źródła chińskiego sukcesu gospodarczego [Between China and the West. An inquiry into the sources of the Chinese economic miracle], Poznań 2018, pp. 103–119, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. The relation between free market economy and democracy has been assumed as a paradigm in the western culture since the Enlightenment. However, this paradigm seems to be violated by markets that flourish under the political dictatorship. Are these markets the exceptions to the rule or maybe their scale does not indicate the necessity of paradigm change? Or maybe we are wrong to assume that capitalism flourish mainly in democratic systems? Is it possible that the relation between communist political dictatorship and liberal economy system is only of temporary nature and people that have economical freedom will demand sooner or later their political freedom? To answer these questions, (1) the paradigm of relationship between free market, its prosperity and democracy and (2) the arguments supporting this relationship have been discussed. Referring to Samuel Huntington’s theory, (3) it has been reminded that many factors, not only economical ones, decide about democratization of political life and some exceptions to this rule have been mentioned. (4) The example of contemporary China is one of the most spectacular example. The short characteristic of (5) its economic condition, (6) its economic system and political dictatorship has been presented and then the attempts have been made to give the arguments either for (7) temporary or (8) permanent relationship between free market and political dictatorship in China. Although the idea of democracy, the rule of law and human rights seems not to be the only alternative base of economical market system, it appears to be prevalent and the only one in a longer period.